A hierarchically co-optimized plan for the enhanced health care system of the year 2000. - Schmitt, O. (IEEE Engineering in medicine and biology magazine)
The paper presents the proposal for a System Reengineered Plan by the year 2000. This plan incorporates sufficient professional security and tolerance to allow "consciousness", at its several levels, to become a regular part of health care procedures; an inflation-adjusted decrease in the annual cost of health care delivery system with at least 50% improved performance and perceived results; a whole-life medical history card; the use of a health care computer with instructional prompting, advice resources, and competence to participate in diagnostic, monitoring, training, therapeutic, and even rehabilitative procedures in the home environment; a full National Strand Epidemiology Library database; a good repertoire of quality of life components organized hierarchically on at least three primary levels of consciousness ordinary perceptive consciousness, multibranch subsconsciousness and at least the first level of superconsciousness; a national awareness and eagerness to accept the possibility of being offered personally adapted life plans; and a well-planned strategies for research and development, marketing, education, and public relations to persuade legislators, academic researchers and educators, and biomedical device and service suppliers, to find rewards and avoid penalties by cooperating with this overall plan or improving and extending it.